Anatomy of the lymphovenous valve of the thoracic duct in humans. Issue 6 (27th February 2020) - O'Hagan, Lomani Archibald; Windsor, John Albert; Phillips, Anthony Ronald John; Itkin, Maxim; Russell, Peter Spencer; Mirjalili, Seyed Ali
Abstract: The majority of lymph generated in the body is returned to the blood circulation via the lymphovenous junction (LVJ) of the thoracic duct (TD). A lymphovenous valve (LVV) is thought to guard this junction by regulating the flow of lymph to the veins and preventing blood from entering the lymphatic system. Despite these important functions, the morphology and mechanism of this valve remains unclear. The aim of this study was to investigate the anatomy of the LVV of the TD. To do this, the TD and the great veins of the left side of the neck were harvested from 16 human cadavers. The LVJs from 12 cadavers were successfully identified and examined macroscopically, microscopically, and using microcomputed tomography. In many specimens, the TD branched before entering the veins. Thus, from 12 cadavers, 21 LVJs were examined. Valves were present at 71% of LVJs (15/21) and were absent in the remainder. The LVV, when present, was typically a bicuspid semilunar valve, although the relative size and position of its cusps were variable. Microscopically, the valve cusps comprised luminal extensions of endothelium with a thin core of collagenous extracellular matrix. This study clearly demonstrated the morphology of the human LVV. This valve may prevent blood from entering the lymphatic system, but its variability and frequent absence calls into question its utility. Further structural and functional studies are required to better define the role of the LVV in health and disease. Abstract : The lymphovenous valve of the thoracic duct (TD), seen from the venous side, and using microcomputed tomography. Our study demonstrated the morphology of this valve in humans, which historically has received little attention. Interest in the TD and the lymphovenous junction (LVJ) is growing as the lymphatic system is understood to play a key role in the promotion of systemic inflammation and organ dysfunction during acute and critical illness. This has implicated the terminal TD and LVJ as locations for potential minimally invasive intervention, highlighting the importance of understanding the anatomy of this area.